Translating Arabic Into English: Basic Considerations in Word Order - Menacere, M. (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractThis paper attempts to discuss the potential difficulties in translating Arabic into English with regard to word order. Arabic has a richer morphology than English and this enables morphological discrimination of surface grammatical relations in a way that is usually impossible in English. As a result, Arabic word order is freer than English with Arabic in general allowing any permutation of the major constituents without loss of grammatically or change in the basic cognitive meaning of the sentence. This paper looks at whether this flexibility in Arabic word order constitutes a translating problem.